Structural analysis systems : software, hardware, capability, compatibility, applications - Niku-Lari, A. (Pergamon, 1986)
Structural Analysis Systems: Software-Hardware Capability-Compatibility-Applications, Volume 3 is a practical guidebook on structural analysis systems and their applications. It provides detailed information about a specific software, its postprocessor capabilities and limitations, computer-aided design connection, and compatibility with the most common computers. Several practical examples from industry with computer and user cost are given.